Classroom Experiment to Determine the Resistivity of an Unknown Metal - Boynazarov, Asliddin; Abdiraxmonov, Shohzamon; Shomaxmatov, Jo’shqin; Khushnazarov, Otabek; Addimuminov, Akmal (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
Electrical resistivity is a fundamental property of materials, reflecting their ability to conduct electricity and playing a critical role in electrical engineering and material science. This experiment investigates the effect of conductor length on resistivity using a single metallic wire with lengths ranging from 10 cm to 60 cm. Resistance was measured for each wire length using a calibrated voltmeter and ammeter, and resistivity was calculated using the relation Equation 1. Experimental conditions were meticulously controlled, with consistent wire material, steady environmental temperature, and precise wire diameter and length measurements to ensure accuracy. The results demonstrate a direct relationship between wire length and resistance, validating the theoretical prediction. The calculated resistivity of the metallic wire was 2.04 x 10-8 Ω⋅m, closely aligning with the theoretical value for silver (1.59 x 10-8 Ω⋅m) and supported by the wire's shiny gray appearance. This experiment highlights the practical application of resistivity in selecting materials for electrical systems and offers a valuable hands-on approach to teaching resistivity concepts in the classroom. The findings can be integrated into physics education to enhance students' understanding of material properties, data analysis, and electrical circuit principles.